2009
DOI: 10.1111/j.1467-8535.2008.00929.x
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of final examinations: A comparative study of closed‐book, invigilated exams and open‐book, open‐web exams

Abstract: Educators have long debated the usefulness (or otherwise) of final examinations; a debate that has typically revolved around the relative merits of closedbook exams, open-book exams, take-home exams or their substitution by some other assessment format (eg, project work). This paper adds a new dimension to the debate by considering how the final examination assessment instrument might be enhanced through harnessing the power of technology, more specifically, how the learner experience of the final examination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
108
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(115 citation statements)
references
References 7 publications
4
108
0
3
Order By: Relevance
“…Since, it increases the students motivation to enhance their performance (study in University of Winchester) [17]. Furthermore, It helps the students in remote area to learn and assess in their locations and it can take it any time, which provide flexibility for students to have the exams [8], [16], [18] . Regarding the students opinion about E-assessment, one of the study conducted using a survey that 88.4% of student prefer E-assessment [19].…”
Section: The Advantages Of Usinf E-assessmentmentioning
confidence: 99%
“…Since, it increases the students motivation to enhance their performance (study in University of Winchester) [17]. Furthermore, It helps the students in remote area to learn and assess in their locations and it can take it any time, which provide flexibility for students to have the exams [8], [16], [18] . Regarding the students opinion about E-assessment, one of the study conducted using a survey that 88.4% of student prefer E-assessment [19].…”
Section: The Advantages Of Usinf E-assessmentmentioning
confidence: 99%
“…While a closed-book exam is probably the most common type of exam in psychology courses, alternative exam types, such as cheat sheets (or crib notes) where the students can prepare notes to use on the exam ahead of time, and open-book exams where the student can use all their material during the test, are increasingly accepted. Students themselves prefer alternative forms of testing, for example, Williams and Wong (2009) found that students prefer open-book exams compared to closed-book tests. Students believed that being able to use notes, cheat sheets and texts during an exam would improve grades and decrease their anxiety.…”
mentioning
confidence: 99%
“…Adgang til hjaelpemidler (laerebøger, internet) under en digital prøve diskuteres også i studiet af Williams & Wong (2009). De beskriver en digital eksamensform, hvor de studerende har adgang til alt undervisningsmateriale og internettet under prøven.…”
Section: Digitale Prøver: De Studerendes Oplevelser Og Perspektiverunclassified